The economics behind the awarding of terminals in seaports: Towards a research agenda - Christophe, Theys; Theo E., Notteboom; Athanasios A., Pallis; Peter W., De Langen (Elsevier, 2010)
Terminal concessions in seaports have only recently gained interest in academic circles. Issues such as the allocation mechanisms (to be) used for granting those concessions, the determination of the concession term and concession fees, as well as the inclusion of special clauses aimed at assuring that the terminal operator will act in the interest of the port authority and the wider community, are increasingly relevant to both academics and the port industry. So far, insights from established economic theories have rarely been applied to terminal concessions in seaports. It, therefore, remains to be seen which kind of awarding procedure would be best for which type of terminal concession. This contribution provides a detailed overview of the different phases of the terminal awarding process, including a classification scheme for awarding procedures, and contains an extensive discussion on the economic issues that require further investigation. The paper concludes by proposing a comprehensive research agenda on the topic. ?